Market Statistics and Technical Analysis: The Role of Volume. - Blume, Lawrence; Easley, David; O'Hara, Maureen (Journal of Finance, 1994)
The authors investigate the informational role of volume and its applicability for technical analysis. They develop a new equilibrium model in which aggregate supply is fixed and traders receive signals with differing quality. The authors show that volume provides information on information quality that cannot be deduced from the price statistic. They show how volume, information precision, and price movements relate, and demonstrate how sequences of volume and prices can be informative. The authors also show that traders who use information contained in market statistics do better than traders who do not. Technical analysis, thus, arises as a natural component of the agents' learning process.